2005
DOI: 10.1111/j.0305-1870.2005.04242.x
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of Endothelial Cyclo‐oxygenase Metabolites in Noradrenaline‐induced Contraction of Rat Coronary Artery

Abstract: 1. Noradrenaline (NA; 0.3 micromol/L) caused a contraction of the rat coronary artery that markedly increased in the presence of the nitric oxide synthase (NOS) inhibitor N(G)-nitro-l-arginine methyl ester (L-NAME; 100 micromol/L) and arachidonic acid (1 micromol/L; P < 0.05). 2. The present experiments attempted to elucidate the endothelium dependency of the contraction and to pharmacologically characterize the factors involved in the contraction induced by NA (0.3 micromol/L) in the presence of L-NAME and ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…After completion of the transmural pressure and imposed flow ranges in APSS (control), the APSS in chamber was replaced with pre‐warmed 38°C APSS containing the nitric oxide synthases (NOS) inhibitor l ‐NAME (Sigma Cat. # N 5751, Sigma‐Aldrich, St. Louis, MO, USA) at 100 μM [1,8,28,31,35,37,38]. The effectiveness of NOS blockade in rat lymphatic vessels induced by application of l ‐NAME at this concentration has been numerously demonstrated by us in previous reports [4,16,20–22].…”
Section: Methodsmentioning
confidence: 99%
“…After completion of the transmural pressure and imposed flow ranges in APSS (control), the APSS in chamber was replaced with pre‐warmed 38°C APSS containing the nitric oxide synthases (NOS) inhibitor l ‐NAME (Sigma Cat. # N 5751, Sigma‐Aldrich, St. Louis, MO, USA) at 100 μM [1,8,28,31,35,37,38]. The effectiveness of NOS blockade in rat lymphatic vessels induced by application of l ‐NAME at this concentration has been numerously demonstrated by us in previous reports [4,16,20–22].…”
Section: Methodsmentioning
confidence: 99%
“…In all experiments the input and output pressure were set equally so flow and shear were only generated by phasic contractions of thoracic duct segments. After completion of the transmural pressure range in APSS (control) we set the transmural pressure at 3 cm H 2 O and APSS in the chamber was replaced with APSS containing the nitric oxide synthase inhibitor l ‐NAME (Sigma N5751; 10 −4 m ; Rees et al 1990; Nakaike et al 1995; Mizuno et al 1998; Datte et al 2005; Wang et al 2005; Watanabe et al 2005; Arenas et al 2006) or with the cyclooxygenase inhibitor, indomethacin (Sigma I7378; 10 −5 m ; Nakaike et al 1995; Mizuno et al 1998; Koller et al 1999; Chan & Von Der Weid, 2003; Tsunemoto et al 2003; Chan et al 2004; Kousai et al 2004).…”
Section: Methodsmentioning
confidence: 99%
“…After completion of the transmural pressure and imposed flow ranges in APSS (control), the APSS in chamber was replaced with APSS containing the nitric oxide (NO) synthase inhibitor l‐NAME (Sigma N 5751) at 10 −4 M [ 2 , 8 , 35 , 37 , 42 , 50 , 51 ]. We used a concentration of l‐NAME at 10 −4 M to be able to compare our data with data obtained in our previous studies [ 19 ] which demonstrated the ability of l‐NAME in this concentration to block completely the contraction‐generated NO‐dependent relaxation in rat thoracic duct.…”
Section: Methodsmentioning
confidence: 99%